COVID-19 and Public Information Behavior - Triyono, Agus (Jogjakarta Communication Conference (JCC), 2023)
The Covid-19 pandemic has changed people's information behavior. It is supported by increasing internet utilization to meet information needs through mass and social media. The media is expected to be able to provide objective, valid, and accurate information so it will not create public anxiety about the pandemic. However, the circulating information related to COVID-19 is making people even more anxious. Even though the need for information during a pandemic is a primary need to be fulfilled. The implications of the availability of information about COVID-19 and the need for health information from the community determine how people carry out information behavior. This study employs a literature review with research and scientific articles as the collected data source. The results showed that based on the review of several studies regarding public information behavior during the Covid-19 pandemic, the use of the internet plays a crucial role in the distribution of information about case developments, handling guidelines, implementation of health protocols, and vaccinations. On the other hand, social media also plays a role in the growth of fake news, making the audience need clarification to determine the correct information quickly.